Professional Development of a Teacher Providing Special Education Support Service: Mentoring - Elif Akay; Hasan Gürgür (Anı Publishing, 2018)
Mentorship provided to increase special education teachers' theoretical knowledge and to better their teaching practice is expected to positively contribute to the quality of educational practice. The aim of this research is to evaluate the mentoring process designed for the professional development of a teacher providing special education support services to students with hearing impairment in an inclusion setting. This study is action research. The participants are the researcher, supported teacher, two hearing impaired students, validity committee and general education teacher. Data has been collected from observations, interviews, researcher diary, documents, and process products. Systematic and critical analysis of data both during and after the research process. Based on research findings, one can suggest that professional development process of teachers who will work in inclusion settings be focused on their individual needs and relevant regulations be arranged in order to support their development through mentoring process.